Leadership Outcomes through the Lens of Workplace Spirituality and Character Development - Waqas Ahmed; Kamran Imtiaz; Muhammad Muzammil; Suleman Muhammad Khan (Inverge Journal of Social Sciences, 2025)
This study examined leadership outcomes through the dual lens of workplace spirituality and character development, highlighting their combined role in enhancing leadership effectiveness. The primary aim was to explore how these constructs influenced leadership practices within organizational contexts. The introduction positioned spirituality and character as complementary frameworks for fostering values-driven leadership in increasingly complex environments. A quantitative research design was employed, utilizing a structured survey administered to 210 respondents across diverse organizational sectors. The measures included validated scales for workplace spirituality, character development, and leadership effectiveness. Descriptive statistics, correlation analysis, and regression modelling were conducted to test the relationships among variables. The results indicated strong positive correlations between workplace spirituality and leadership effectiveness, as well as between character development and leadership outcomes. Among the predictors, character development demonstrated the strongest effect, highlighting the importance of virtues such as integrity and accountability. Furthermore, the interaction of spirituality and character revealed a synergistic influence on leadership, underscoring the significance of integrating both dimensions into leadership development practices. The study concluded that leadership effectiveness is best cultivated when organizations promote both spiritual awareness and character-based competencies. Future research was recommended to employ longitudinal and cross-cultural approaches, offering deeper insights into the evolving dynamics of spirituality, character, and leadership in global contexts. References Afsar, B., & Rehman, M. (2017). The impact of workplace spirituality on organizational citizenship behaviors and knowledge-sharing intention: The mediating role of affective commitment. Journal of Management, Spirituality & Religion, 14(3), 244–263. https://doi.org/10.1080/14766086.2017.1314819 Ahmad, A., & Khan, M. (2021). Workplace spirituality and job outcomes: The mediating role of work engagement. Journal of Organizational Effectiveness: People and Performance, 8(1), 23–40. https://doi.org/10.1108/JOEPP-04-2020-0023 Ashmos, D. P., & Duchon, D. (2000). Spirituality at work: A conceptualization and measure. Journal of Management Inquiry, 9(2), 134–145. https://doi.org/10.1177/105649260092008 Asif, M., Shah, H., & Asim, H. A. H. (2025). Cybersecurity and audit resilience in digital finance: Global insights and the Pakistani context. Journal of Asian Development Studies, 14(3), 560–573. https://doi.org/10.62345/jads.2025.14.3.47 Binu Raj, A., Ambreesh, P., Tripathi, N. N., & Ambreesh Kumar, A. (2023). Workplace spirituality and job satisfaction among teachers: Influence of well-being and spiritual leadership. International Journal of Educational Management, 37(6/7), 1303–1322. https://doi.org/10.1108/IJEM-03-2023-0110 Cameron, K. S. (2011). Responsible leadership as virtuous leadership. Journal of Business Ethics, 98(1), 25–35. https://doi.org/10.1007/s10551-011-1023-6 Crossan, M., Byrne, A., & Seijts, G. (2024). Developing leader character. Academy of Management Learning & Education, 23(1), 35–56. https://doi.org/10.5465/amle.2023.0520 Crossan, M., Byrne, A., Seijts, G., Reno, M., Monzani, L., & Gandz, J. (2023). Toward a framework of leader character in organizations. The Leadership Quarterly, 34(1), 101647. https://doi.org/10.1016/j.leaqua.2022.101647 Crossan, M., Byrne, A., Seijts, G., Sturm, R. E., & others. (2024). Developing leader character: Finding a way forward. Academy of Management Learning & Education, 23(1), 35–56. https://doi.org/10.5465/amle.2023.0520 Elsetouhi, A., Hammad, A., & Nagm, A. (2021). Leadership, spirituality, and employee outcomes: The role of workplace spirituality in Egypt. Journal of Management, Spirituality & Religion, 18(2), 179–201. https://doi.org/10.1080/14766086.2020.1839747 Fernando, M. (2011). Spirituality and leadership: Concepts and models. Journal of Management, Spirituality & Religion, 8(3), 233–246. https://doi.org/10.1080/14766086.2011.599146 Fernando, M., & Jackson, B. (2019). Understanding spiritual leadership in workplace: Insights from Sri Lanka. Journal of Business Ethics, 155(3), 779–795. https://doi.org/10.1007/s10551-017-3516-z Fry, L. W. (2003). Toward a theory of spiritual leadership. The Leadership Quarterly, 14(6), 693–727. https://doi.org/10.1016/j.leaqua.2003.09.001 Garg, N. (2023). Workplace spirituality: A systematic review and future research agenda. Journal of Organizational Change Management, 36(4), 789–808. https://doi.org/10.1108/JOCM-04-2022-0128 Gupta, M., & Kumar, V. (2020). Exploring the impact of workplace spirituality on job stress and satisfaction: A study of academic professionals. Journal of Human Values, 26(1), 46–64. https://doi.org/10.1177/0971685819893771 Kiel, F. (2015). Return on character: The real reason leaders and their companies win. Harvard Business Review Press. Kinjerski, V. (2020). The spirit at work scale: Developing and validating a measure of individual spirituality at work. Journal of Management, Spirituality & Religion, 17(4), 327–348. https://doi.org/10.1080/14766086.2020.1724199 Latif, A., Ullah, R., Ahmed, I., Rehman, J. ur, & Khan, H. U. (2024). Workplace spirituality: A catalyst for job satisfaction? Exploring cultural and gender contingencies. Research Journal for Societal Issues, 6(3), 241–262. https://doi.org/10.56976/rjsi.v6i3.281 Syahir, A. N. A., Abidin, M. S. Z., Sa’ari, C. Z., & Rahman, M. Z. A. (2025). Workplace Spirituality and Its Impact on Employee Well-Being: A Systematic Literature Review of Global Evidence. Journal of Religion and Health, 1-33. https://doi.org/10.1007/s10943-025-02350-2 Malik, N., Rafiq-uz-Zaman, M., Bugti, M. A., & Bangulzai, W. A. (2025). Harassment of women in South Punjab politics: Impacts and strategies for enhanced leadership. ACADEMIA International Journal for Social Sciences, 4(3), 2575–2590. https://doi.org/10.63056/ACAD.004.03.0547 Milliman, J., Gatling, A., & Kim, J. (2018). The effect of workplace spirituality on hospitality employee engagement, intention to stay, and service delivery. Journal of Hospitality and Tourism Management, 35, 56–65. https://doi.org/10.1016/j.jhtm.2018.03.002 Mo, S., & Shi, J. (2017). Linking ethical leadership to employee burnout, workplace deviance and performance: Testing the mediating roles of trust in leader and surface acting. Journal of Business Ethics, 144(2), 293–303. https://doi.org/10.1007/s10551-015-2821-z Mohammed, S. M., & Elashram, R. E. (2022). The impact of spiritual leadership on workplace spirituality in the light of the COVID-19 pandemic in the governmental health sector. Leadership & Organization Development Journal, 43(4), 623–637. Oxford Character Project Report. (2023). Character-based leadership and leadership development in low- and middle-income countries. Oxford Character Project. https://oxfordcharacter.org/research/character-global-leadership-report-2023?utm_source=chatgpt.com Pavlovich, K., & Krahnke, K. (2019). Spirituality, sustainability, and leadership: Insights for the future of responsible business. Journal of Business Ethics, 155(3), 703–715. https://doi.org/10.1007/s10551-017-3515-0 Petchsawang, P., & Duchon, D. (2009). Measuring workplace spirituality in an Asian context. Human Resource Development International, 12(4), 459–468. https://doi.org/10.1080/13678860903135912 Piwowar-Sulej, K., & Iqbal, Q. (2024). A systematic literature review on spiritual leadership: antecedents, mechanism, moderators and outcomes. Journal of Organizational Change Management, 37(8), 18–35. https://doi.org/10.1108/JOCM-11-2023-0483 Polish Workers Study. (2024). Spirituality, organizational gratefulness, and well-being among Polish workers. Journal of Religion and Health, 63, 4130–4155. https://doi.org/10.1007/s10943-024-02036-1 Rafiq-uz-Zaman, M., Bano, S., & Naveed, Y. (2025). Comparative analysis of authoritative and democratic leadership styles and their impact on school management effectiveness. Inverge Journal of Social Sciences, 4(2), 105–117. https://doi.org/10.63544/ijss.v4i2.132 Rahman, M., Hossain, M., & Zaman, S. (2022). Workplace spirituality and employee outcomes: A systematic literature review. Management Research Review, 45(4), 489–508. https://doi.org/10.1108/MRR-02-2021-0155 Reave, L. (2005). Spiritual values and practices related to leadership effectiveness. The Leadership Quarterly, 16(5), 655–687. https://doi.org/10.1016/j.leaqua.2005.07.003 Rego, A., Pina e Cunha, M., & Simpson, A. V. (2021). The perceived impact of leaders’ humility on team effectiveness: The mediating roles of team voice and performance pressure. Journal of Business Research, 128, 142–152. https://doi.org/10.1016/j.jbusres.2021.01.065 Samul, J. (2024). Spiritual leadership, work engagement, and well-being: The mediating role of workplace spirituality. Central European Management Journal, 32(2), 191–204. https://doi.org/10.1108/CEMJ-05-2023-0223 Sarwar, S., Nisar, Q. A., & Malik, O. F. (2022). Exploring the impact of ethical leadership and leader-member exchange on employee outcomes: The mediating role of organizational identification. European Journal of Management and Business Economics, 31(2), 147–163. https://doi.org/10.1108/EJMBE-08-2020-0255 Seijts, G., Gandz, J., Crossan, M., & Reno, M. (2020). Character matters: Character dimensions’ impact on leader effectiveness. Journal of Business Ethics, 166(3), 565–584. https://doi.org/10.1007/s10551-019-04138-7 Wang, Z., Xu, H., & Liu, Y. (2018). Spiritual leadership and employee innovative behavior: The role of psychological empowerment and innovation climate. Frontiers in Psychology, 9, 2627. https://doi.org/10.3389/fpsyg.2018.02627 Zhang, Y., & Zhang, J. (2019). How spiritual leadership boosts proactive workplace behavior: The mediating role of organizational identification and psychological safety. Frontiers in Psychology, 10, 1206. https://doi.org/10.3389/fpsyg.2019.01206